2017
DOI: 10.3389/fphys.2017.00641
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid EMD-Kurtosis Method for Estimating Fetal Heart Rate from Continuous Doppler Signals

Abstract: Monitoring of fetal heart rate (FHR) is an important measure of fetal wellbeing during the months of pregnancy. Previous works on estimating FHR variability from Doppler ultrasound (DUS) signal mainly through autocorrelation analysis showed low accuracy when compared with heart rate variability (HRV) computed from fetal electrocardiography (fECG). In this work, we proposed a method based on empirical mode decomposition (EMD) and the kurtosis statistics to estimate FHR and its variability from DUS. Comparison b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Our results revealed that if the number of features in SVM increases, the specificity incearses by 16.5% and the precision of the classification increases by 11.5% as compared to the reference results obtained by [CostaEn, SampEn] features [5], [6], [7], however the sensitivity decreases. This decrase in sensitivity supports the findings of Al-Angari et al [13] which showed that such types of kurtosis-based features are not only sensitive to detect IUGR but also sensitive to cardiac diseases. Kurtosis results were precise (55-100 %) which is in agreement with the work done by Fan and Zuo [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results revealed that if the number of features in SVM increases, the specificity incearses by 16.5% and the precision of the classification increases by 11.5% as compared to the reference results obtained by [CostaEn, SampEn] features [5], [6], [7], however the sensitivity decreases. This decrase in sensitivity supports the findings of Al-Angari et al [13] which showed that such types of kurtosis-based features are not only sensitive to detect IUGR but also sensitive to cardiac diseases. Kurtosis results were precise (55-100 %) which is in agreement with the work done by Fan and Zuo [17].…”
Section: Discussionsupporting
confidence: 88%
“…Kurtosis is the measure of the thickness or heaviness of the tails of a distribution of the signal, and the measure of the "tailedness" of the probability distribution [13]. Kurtosis is a descriptor of the shape of a probability distribution.…”
Section: F Kurtosismentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical mode decomposition (EMD) [48], which corresponds to a previous version of this technique, has been used in different biomedical engineering approaches [49]. Particularly, in FHR signal analysis it has been used for FHR estimation from Doppler Ultrasound signals [57], analysis of the FHR signal components in order test the reliability of the EMD performance [58], FHR baseline estimation with analysis of fetal movements [59], assessment of the high frequency FHR information [60], enhancement of the CTG signal quality by reducing signal artifacts [50], and FHR signal feature extraction and classification [49,61]. These works have concluded that EMD could be appropriate for the analysis of the FHR signal components in the time-domain.…”
Section: Fhr Signal Decomposition and Tv-ar Spectrum Computationmentioning
confidence: 99%
“…Marzbanrad et al (2014) proposed an automated estimation of fetal cardiac intervals from a DUS signal based upon a unique combination of empirical mode decomposition (EMD) and hybrid support vector machine-hidden Markov model(SVM/HMM). Al-Angari et al (2017) proposed a new method based on EMD and kurtosis statistics to estimate fetal heart rate and variability of fetal Doppler ultrasound signal, showing excellent performance in estimating fetal beat to beat interval. Recently, Seong (2018) has disclosed a method for extracting fetal heart rate in, in which average magnitude difference function (AMDF) and ACF are used.…”
Section: Introductionmentioning
confidence: 99%